Protein expression of c-erbB-2 and p53 in normal ducts, ductal carcinoma in situ and invasive carcinoma of the same breast - Menezes, Marcus Vinicius Martins de (2006)
CONTEXT AND OBJECTIVE: Breast cancer is thought to derive from progressively aberrant, non-invasive breast lesions, but it is not known exactly how invasive breast cancer develops from these lesions. The aim of this study was to verify the changes in c-erbB-2 and p53 protein expression between non-neoplastic ducts, ductal carcinoma in situ and invasive ductal carcinoma found in the same breast. DESIGN AND SETTING: This was a cross- sectional study at Centro de Atenção Integral à Saúde da Mulher, Campinas, Brazil. METHODS: Fifty-six women with invasive ductal carcinoma and ductal carcinoma in situ in the same breast were included. The expression of c-erbB-2 and p53 proteins was assessed in non-neoplastic and neoplastic cells using im- munohistochemical techniques. RESULTS: The c-erbB-2 protein was absent in non-neoplastic ducts but was present in 46% and 36% of in situ and invasive carcinoma compo- nents, respectively. Only 2% of non-neoplastic ducts, and 18% and 16% of ductal carcinoma in situ and invasive carcinoma components, respectively, were positive for p53 protein. No significant difference in c-erbB-2 and p53 protein expression was observed between in situ and invasive components. The nuclear grade agree- ment between in situ and invasive carcinoma was very good. CONCLUSIONS: The invasiveness of ductal carcinoma in situ seems to be independent of the Her-2/neu and TP53 genes. The general features of an occurrence of breast carcinoma are formulated at the outset of carcinogenesis, and the Her-2/neu and TP53 genes are involved.